Economic Losses from Insect Pest Infestation on Rice Stored on-farm in Benin - Togola, A.; Seck, P.A.; Glitho, I.A.; Diagne, A.; Adda, C.; Touré, A.; Nwilene, F.E. (Science Alert, 2013)
In Benin, on-farm storage of paddy rice is increasingly exposed to pest damage. Insect infestation causes a loss of income to farmers and other post-harvest stakeholders. The objective of this study is to assess the magnitude of damage caused to rice stored on-farm and evaluate the potential economic risk. In this study, 65 stocks of paddy rice were inspected and sampled in order to assess the economic losses. In addition, an agronomic survey was carried out to determine producer perceptions about the economic impact of stored rice pests in a farming environment. The findings show that weight loss amounts to 5.47% after 6 months of storage in the southern region, 4.07% in the central region and 1.64% in the northern region. From an economic perspective, 6 months duration of storage is likely to cause an estimated loss of 21,315 FCFA (Franc of the African Financial Community) per ton of paddy in the South region, compared to losses of 8,088 FCFA in the North. Furthermore, 36.92% of farmer respondents consider that these insects cause considerable economic damage to stored rice. This study made it possible not only to assess current losses attributable to insect pests in the country but also to obtain future projections about trends in high-risk regions. These findings will undoubtedly pave the way for future research in improved stored rice protection and income safeguards for various stakeholders intervening in the post-harvest sector.